Diversity of Malaysian Lentinus fr. and chemical analysis of antioxidative extract from mycelia of Lentinus squarrosulus mont. / Sumaiyah Abdullah - Abdullah, Sumaiyah (2014)
Lentinus species of Peninsular Malaysia were studied from April 2003 to June 2008 at 35 localities in Kedah, Perak, Selangor, Pahang, Johor, Negeri Sembilan, and Kelantan states and in the Federal Territory of Kuala Lumpur. Macro and micro-morphological features were used to identify the collections to species level. Seventy-eight Lentinus specimens comprised in ten species. Lentinus squarrosulus was commonly found being collected from almost all study sites except in Negeri Sembilan. Lentinus fasciatus was documented as a new record for Peninsular Malaysia. Five out of ten Lentinus species namely L. fasciatus, L. polychrous, L. sajor-caju, L. squarrosulus and L. strigosus were successfully cultured. Studies were performed to evaluate antioxidant capacities using Folin-Ciocalteu assay, scavenging effects on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, ß-carotene-linoleate bleaching assay, cupric ion reducing antioxidant capacity (CUPRAC), reducing power assay and lipid peroxidation assay. Preliminary study of five mixed methanol and dicloromethane extracts of mycelia of Lentinus species showed that L. fasciatus and L. squarrosulus exhibited the most potent antioxidant capacities. The L. squarrosulus extract performed best in the Folin-Ciocalteu assay (58.23 mg GAE/g). The Lentinus fasciatus extract exhibited the highest radical-scavenging activity of IC50 (14.17 mg/mL) followed by the L. squarrosulus extract (29.13 mg/mL). Lentinus fasciatus extract at a concentration of 1 mg/mL also exhibited the highest reducing capability on cupric (CUPRAC assay) and ferric ion (Reducing power assay) with absorbance values of (A450, 1.22) and (A700, 0.65) respectively, while the L. squarrosulus extract had the highest antioxidant activity against lipid peroxidation assay with 70.06% inhibition at 10 mg/mL concentration. This extract also showed the highest value of antioxidant activity based on β-carotene bleaching assay with EC50 value of 0.02 mg/mL. Consequently, L. fasciatus and L. squarrosulus were further investigated to determine the antioxidant capacity of polar and non-polar components using methanol and dichloromethane. In the Folin-Ciocalteu assay, Lentinus fasciatus dichloromethane extract (LfDCM) showed the highest result (98.43 mg GAE/g) followed by Lentinus squarrosulus methanolic extract (LsqMeOH) (46.43 mg GAE/g), while LsqMeOH exhibited the highest antioxidant activity as determined by lipid peroxidation assay (50.27%), β-carotene (75.50%), 1,1-diphenyl-2-picrylhydrazil (DPPH) radicals scavenging ability (94.73%) and ferric reducing power (A700, 0.30). In the cupric reducing assay, L. squarrosulus dichloromethane extract (LsqDCM) exhibited the highest reducing power at 1 mg/mL (A450, 0.87), but was not significantly different from the LsqMeOH extract (A450, The present study indicated that LsqMeOH extract showed stronger antioxidant capacities as compared to other extracts. CUPRAC-guided purification was performed on LsqMeOH by using thin layer chromatography (TLC) and reversed phase-high performance liquid chromatography (RP-HPLC). Using TLC, four fractions were separated exhibiting absorbance values (A 0.84). 450) of 0.75 (FR3-TLC), 0.73 (FR1-TLC), 0.68 (FR4-TLC) and 0.67 (FR2-TLC) at 1 mg/mL. On the other hand, using RP-HPLC, three fractions were separated namely as FR1-RP-HPLC, FR2-RP-HPLC and FR3-RP-HPLC exhibiting absorbance values (A450) of 0.21, 0.86 and 0.36 respectively at 1 mg/mL. These findings revealed that separation of the components (by TLC or RP-HPLC) reduced the antioxidant potential of the fraction suggesting the effects of the components can be additive - if not synergistic. The chemical constituents of LsqMeOH, FR3-TLC and FR2-RP-HPLC were effectively identified by LC-MS/MS. A type of ganoderic acid was detected from the LsqMeOH, FR3-TLC and FR2-RP-HPLC extracts. Three peaks in FR3-TLC that have the same [M-H]- ion at m/z 696 were observed to share some distinct fragment ions that were characteristic of ganoderic acid type. Uridine compound with mass fragments at m/z 225, 200 and 140 was present in both FR3-TLC and FR2-RP-HPLC, while in FR2-RP-HPLC, three peaks identified have masses corresponding to flavanoid compounds. Phenolic acids are the main class of compounds from LsqMeOH that contributed to antioxidant activities. Ganoderic acid, uridine and flavanoid were identified for the first time in L. squarrosulus antioxidative fractions. Therefore, this research suggested the potentials of L. squarrosulus as a source of antioxidant extract to be used either in food industries (nutraceuticals and functional food) or cosmetic products.